Far‐field potentials in hypothenar motor unit number estimation. Issue 2 (4th February 2013) - Higashihara, Mana; Sonoo, Masahiro; Yamamoto, Tomotaka; Kawamura, Yasuomi; Nagashima, Yu; Terao, Yasuo; Kaida, Kenichi; Kimura, Fumihiko; Ugawa, Yoshikazu; Tsuji, Shoji
ABSTRACT Introduction: Contamination by far‐field potentials (FFPs) may interfere with motor unit number estimation (MUNE) in the ulnar nerve. Methods: Surface motor unit potentials (SMUPs) from 29 spinal and bulbar muscular atrophy (SBMA) patients and 27 control subjects were classified into SMUPs from the abductor digiti minimi muscle (ADM SMUPs) or non‐ADM SMUPs, based on the waveform patterns from 3‐channel recordings. Results: The mean areas of the ADM SMUPs and non‐ADM SMUPs in control subjects were 219.0 ± 131.3 and 63.7 ± 48.5 μVms, respectively. In SBMA patients they were 1988.9 ± 999.4 and 222.7 ± 125.7 μVms, respectively. The percentages of non‐ADM SMUPs were 68 ± 22% in controls and 84 ± 15% in SBMA patients. Conclusions: Non‐ADM SMUPs generated mainly by FFPs often had a negative onset in the routine lead and were indistinguishable from ADM SMUPs. More frequent exclusion of smaller non‐ADM SMUPs in controls by size criteria would reduce the diagnostic yield of MUNE. Muscle Nerve, 48: 191–197, 2013